Prevention And Detection Mechanism For Security In Passive Rfid System - Khor, Jing Huey (2013)
Low-cost radio frequency identification (RFID) tags conforming to the EPCglobal Class-1 Generation-2 standard are inherently insecure due to computational constraints. This thesis proposed the use of both prevention and detection mechanisms to solve the security and privacy issues. A lightweight cryptographic mutual authentication protocol which is resistant to tracking, denial of service (DoS) and replay attacks is proposed as a prevention mechanism. The proposed protocol is designed with lightweight cryptographic algorithm, including XOR, Hamming distance, rotation and a modified linear congruential generator (MLCG). The proposed protocol using 64 bits index is proved having the lowest non-unequivocally identification probability. In addition, the randomness of the session key generated from the MLCG is verified using NIST test suite. Besides that, the security of the proposed protocol is validated using the formal analysis tool, AVISPA. The correctness of the proposed protocol is demonstrated in a simulation model developed in JAVA TCP/IP socket. Next, the proposed protocol is implemented in RFID system including IAIK UHF Demo tag, TagSense Nano-UHF reader and back-end database. A GUI is created in a form of JAVA application to display data detected from tag. The proposed protocol implemented in real RFID system outperforms other related protocols because of 13.46 % shorter read time and write time consumed. The system is proved to be able to prevent tracking, DoS, and replay attacks from adversaries with moderate computation requirement compared to other related protocols.